TEACHING AND FACILITATION STRATEGIES FOR THE PROFESSIONAL SOCIALISATION OF STUDENT NURSES - De Swardt, HC; van Rensburg, GH; Oosthuizen, MJ (South African Journal of Higher Education, 2016)
A fundamental goal of professional socialisation in student nurses is to enhance nursing conduct and quality of care. Professional socialisation requires internalisation of characteristics typical of a profession when a student nurse learns and applies knowledge, skills, norms and values. The success of professional socialisation lies in the quality of teaching and learning. The quantitative phase of a sequential mixed methods study revealed the perceptions of nurse educators regarding their role in teaching and facilitation of professional socialisation. Findings informed the development of guidelines to support educators in planning and implementing teaching and facilitation strategies. Strategies should incorporate values and beliefs of the nursing profession, be student centred, take cognisance of the hidden curriculum and utilise various teaching, facilitation and assessment methods. The role of the educator in supporting students in a positive and empowering manner becomes imperative for professional socialisation of students.